Tradisi Pendidikan Pesantren dalam Mengembangkan Jiwa Kepemimpinan Profetik - Abidin, Zainal; Sirojuddin, Akhmad (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
Prophetic leadership is a need of society in the modern era dominated by secular values oriented to the needs of the world. The purpose of this study is to analyze and describe the values developed in pesantren, pesantren traditions, and the implementation of pesantren education in developing the spirit of prophetic leadership. This research uses a qualitative approach with a case study type. The case referred to in this study is the intertwining system built in the Darullughah wadda'wah Islamic boarding school which has an integration between the pesantren education system and the higher education system. Data collection techniques were carried out through participant observation, interviews with key informants, and documentation. The results of this data collection were analyzed through condensation, display, and verification. To test the validity of the data, this research conducted triangulation, peer discussion, and extended research observation. The results of this study indicate that the values developed are (1). Integrity values, (2) friendship values, (3) jihad values, (4) taqwa values, (5) moral values. The traditions developed by the pesantren are (1) the bahtsul masa'il tradition, (2) the tradition of developing a religious culture, (3) the Khidmah tradition, and (4) the da'wah tradition. While the implementation is (1) curriculum development, both extra-curricular, co-curricular, and extracurricular, (2) leadership training such as communication skills, decision making, task delegation, team leadership, and conflict resolution, (3) development of communication skills, (4) personality development, (5) mentorship, and (6) evaluation and feedback.